Post COVID-19 Infection in Subclinical Hyperthyroidism among Patients Attending a Tertiary Hospital in Kathmandu (Nepal Medical College Journal, 2024)
Coronavirus disease 2019 (COVID-19) infection may induce thyroid dysfunction as Coronavirus 2 (SARS-CoV-2) can invade the human tissue cells through the cell receptor of angiotensin-converting enzyme 2 (ACE2), expression of which is high in thyroid tissue. The aim of the present study was to assess the subclinical hyperthyroidism post-COVID-19 effects on thyroid function in patients without history of thyroid disease after complete recovery from mild-to-severe COVID19 and find the prevalence of subclinical hyperthyroidism. A descriptive cross-sectional study was conducted in the Department of Internal Medicine, of tertiary care center from September 2022 to February 2023 after obtaining ethical approval from the Institutional Review Committee of Nepal Medical College (Ref. No.: 15-079/080). Convenience sampling method was used among patients who met the eligibility criteria. Point estimate at 95.0% confidence interval were calculated along with frequency and proportion for binary data. Out of 38 patients, 34 (89.5%) had thyroid dysfunction. Among them, 7 (20.6%) had subclinical hyperthyroidism, 2 (5.9%) had thyroiditis and 1 (2.9%) had Graves’ disease. Those who had thyroid dysfunction, 10 (29.4%) people were diagnosed with hyperthyroidism. The hyperthyroidism among COVID-19 patients is a common finding and subclinical hyperthyroidism was seen in 20.6% of patients post COVID-19. Therefore, while managing COVID-19, patients’ thyroid profile should be considered.